ILRI and the UNFSS: Why livestock matter - International Livestock Research Institute (International Livestock Research Institute, 2021)
Nutritious diets are the basis of health & prosperity. Food choice shouldn't be a privilege – but it is. Livestock are needed to ensure access to nutrition for people in poor countries to meet the SDG 2030 Agenda. #whylivestockmatter #UNFSS2021